Study of Morphometric Tectonic Indicators of the Wadi Al-Hay Basin in the Najaf desert using GIS data - Latif Jabbar Farhan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The research dealt with the morpho-tectonic indicators of the Wadi Al-Hay basin and identified the nature of the effectiveness the tectonics activity ,using mathematical equations for the Geomorphological indicators of that Valley ,   through which it is inferred that tectonic activity occurred in the study area ,based on the Digital Elevation Model(DEM) and the ArcGIS10.8 ,Program. The results of the study appeared within the basin that the region is witnessing Tectonic stability as it is located within the stable platform though the use of several indicators ,namely (AF,T,SL,VF),and the values of the basin were recorded within the low degree and reached (62.38,0.66,400.79,13.102),which indicates a decreases in tectonic activity in the basin area.DOI: https://doi.org/10.54633/2333-025-058-009